Perancangan Buku Pembelajaran Aksara Jawa untuk Meningkatkan Minat Belajar Remaja dan Pelestarian Budaya Jawa - Rosalia Nadya Narulita; Aditya Nirwana; Bintang Pramudya PP (Program Studi Desain Komunikasi Visual, Fakultas Sains dan Teknologi, Universitas Ma Chung, 2019)
Javanese script now has faded. Javanese script currently used to elementary schools, besides that, Javanese script book references are very few and it difficult to someone who wants to learn Javanese script. Therefore, Javanese script learning book was designed to increase the interest of learning in adolescent, also to preserve Javanese culture. This design uses qualitative methods that produce primary and secondary data. It begins with research, analysis, synthesis, design of content concepts, visual concepts, design design concepts, final design and production. It will produce Javanese script learning book for beginners. This book uses six types of paper, book size 148mm x 210 mm with softcover. Media supporters are worksheets, typeface, poster typeface, fabric sign, motion graphic and social media promotion. This book has been tested for effectiveness through qualitatively questionnaire and concluded that the visual aspect change the stigma of learning Javanese scripts that was bored to fun learning.